1997
DOI: 10.1016/s1010-7940(97)00273-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness polyneuropathy: a new iatrogenically induced syndrome after cardiac surgery?

Abstract: CIP, despite it's benign nature due to it's spontaneous remission in patients who survive, is a disturbing complication following cardiac surgery which is associated with high mortality, a prolonged stay in the ICU, as well as an extended time on ventilator support. Interventions like chronic hemodiafiltration, the application of corticosteroids and the administration of high doses of catecholamines are more frequent in patients with CIP. Whether this indicates a causal relationship remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
0
14
0
7
Order By: Relevance
“…In contrast, in a group of cardiac surgical patients the use of renal replacement therapy was more frequent in those diagnosed with CIP, although the incidence of sepsis and the severity of the process were significantly higher than in the control group [28]. Since the number of patients with renal failure and the severity of this process were similar in the two groups, the likely explanation of our finding is that the use of renal replacement therapy allows for the control of metabolic disturbances or is a means of eliminating a low-molecular toxic agent that might be implicated in CIP development [29].…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, in a group of cardiac surgical patients the use of renal replacement therapy was more frequent in those diagnosed with CIP, although the incidence of sepsis and the severity of the process were significantly higher than in the control group [28]. Since the number of patients with renal failure and the severity of this process were similar in the two groups, the likely explanation of our finding is that the use of renal replacement therapy allows for the control of metabolic disturbances or is a means of eliminating a low-molecular toxic agent that might be implicated in CIP development [29].…”
Section: Discussionmentioning
confidence: 69%
“…The contribution of CINMA to prolonged mechanical ventilation has been studied in 10 cohorts of ICU patients [54,56,[65][66][67][68][69][70][71][72]. Four studies have shown an association between CINMA and an increased duration of weaning or weaning failure [49,67,70,71].…”
Section: Peripheral Dysfunctionmentioning
confidence: 99%
“…44 Aminoglycoside antibiotics were associated with paresis in a single study; however, additional observational studies demonstrated no significant association. 6,34,36,39,40 There are single studies suggesting that other potentially modifiable ICU interventions, including liberal fluid administration and transfusion, journal.publications.chestnet.org may contribute to ICUAW, although these associations need verification in larger patient cohorts. 45,46 Prolonged immobilization is associated with atrophy in patients who are critically ill.…”
Section: In-hospital Risk Factors For Icuawmentioning
confidence: 99%